The effect of the variation of muscle elongation exercises on the base efficiency and metabolic rate of elite handball players - Jassim Mkhilf Al-Shihany, Alaa (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to prepare exercises that reconsider the training of muscle elongation ranges in line with the requirements of improving the cellular biochemical system, so that the researcher assumes that these exercises have a positive effect in improving the cellular base efficiency and their metabolism rate, and the experimental approach was adopted by designing the experimental and control group on a sample of 12 players Handball was deliberately chosen by (85.714%) from their specific community of handball players affiliated with the Iraqi national team participating in the sports season (2019) competitions. The approved tests were to measure the concentration of lactic acid and sodium bicarbonate in a laboratory after (5) minutes after a physical effort on the treadmill. Moving at a speed of 7 km /h directly and measuring (RMR) at rest time without any physical effort with the Fitmate Pro system from the company (COSMED) for global sports physiological laboratories, and exercises were prepared for (10) consecutive weeks at a rate of (4) units per week And after the end of the experiment and treating its results with the SPSS system, the extracts and applications were that the contrast of muscle stretching exercises had a positive effect in reducing the level of lactic concentration and improving the investment in energy production Corresponding to the high concentration of sodium bicarbonate, thus increasing the level of basal efficiency of elite handball players, and the positive effect on the level of basal competence as a result of the variation in muscle stretching exercises has a role in increasing the level of cellular metabolism of elite handball players. The hand is taken into account when planning pregnancy cycles, especially for muscle stretching or for violent exercises that they receive during the special preparation period.